Ceilândia/DF : histórias, afetos e (re)significações a partir da educação patrimonial - Rodrigues, Sandra Maria (2021)
The present research starts from the study of the history of women from Heritage Education, using as a tool the participatory inventories of cultural heritage and female memories about the construction of the then satellite city of Ceilândia, peripheral zone of the Federal District, and its cultural heritage, linked, for the most part, to the construction of the dignity and citizenship of its residents, made available by the Public Archives of the Federal District - APDF. In addition to previously selected female memories, the actions developed in a 2nd year high school class at the public educational institution Centro Educational Incra 09, located in the rural area of the Ceilândia administrative region, aim to promote knowledge and appreciation of cultural heritage and history local analyzing the role played by women as transmitters of values, knowledge, and stories in the administrative region of Ceilândia - DF. In classes-workshops, the local history of Ceilândia was worked on, which is selected from an Invaders Eradication Campaign - CEI, concepts of the axes and structuring of the project, as well as the analyzes and reflections of the students, elaborated in Contribute to the Vision of the memories and stories of women and their views on Ceilândia and its inhabitants as producers of culture.